2022
DOI: 10.1021/acssuschemeng.2c03063
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Engineering of Yarrowia lipolytica for Sustainable Production of α-Bisabolene from Waste Cooking Oil

Abstract: Metabolic engineering of yeasts for terpenoid production has mostly focused on the cytoplasm, whereas harnessing their organelles as subcellular factories has been overlooked. Herein, the farnesyl diphosphate synthetic pathway and α-bisabolene synthase were compartmentalized into the oleaginous yeast Yarrowia lipolytica's mitochondria to enable high-level α-bisabolene production. Through comprehensive metabolic engineering approaches, we exploited the potential and capability of the mitochondria as a subcellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Zhao et al found that the single overexpression of ERG19 could improve the bisabolene production in Y. lipolytica strain harboring only the bisabolene synthase . Guo et al found that the titers of (+)-valencene and (+)-nootkatone in Y.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Zhao et al found that the single overexpression of ERG19 could improve the bisabolene production in Y. lipolytica strain harboring only the bisabolene synthase . Guo et al found that the titers of (+)-valencene and (+)-nootkatone in Y.…”
Section: Resultsmentioning
confidence: 99%
“…5 For example, harnessing the organelle-derived acetyl-CoA was proven to be able to enhance acetyl-CoA availability and successfully increased the titers of α-humulene and amorpha-4,11-diene to 21.7 g/L and 427 mg/L in Yarrowia lipolytica and S. cerevisiae with the combination of cytoplasmic and peroxisomal or mitochondrial engineering. 6,7 Besides, integration of strengthening the MVA pathway and repressing the com-petitive sterol biosynthesis strongly supported the FPP flux toward target sesquiterpene production in S. cerevisiae or other yeasts, such as trans-nerolidol, 8−10 amorphadiene, 11,12 bisabolene, 13 farnesene, 14,15 α-santalene, 16,17 caryophyllene, 18 and longifolene. 19 The rate-limiting steps identified in the above studies include almost all of the genes related to the MVA pathway but varied with the specific sesquiterpene and yeast host.…”
Section: ■ Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…These results are in accordance with a previous study conducted by Cao et al In our previous study, we demonstrated that the ABC-G1 transporter fromGrosmania clavigera effectively mitigated cytotoxicity and increased the overall production titer of α-bisabolene in engineered Y. lipolytica. , Here, we overexpressed the ABC-G1 transporter in strain Po1gαB1, and the intracellular α-bisabolene production was decreased from 5.82 to 1.65 mg/L (Figure S4). According to Figure B, strain Po1gαB2 produced approximately 97.5 mg/L of α-bisabolene after 5 days of fermentation in YPD medium, representing a 3.9-fold increase in α-bisabolene titer compared to the control strain Po1gαB0 (20.1 mg/L) (Figure B).…”
Section: Results and Discussionmentioning
confidence: 99%